Aspek Hukum Perjanjian Kredit Pada Koperasi - I Gusti Agung Wisudawan (Fakultas Hukum Universitas Mataram, 2012)
The credit agreement offered by corporation is significant to enhance its member’s welfare as well as sustainability of small and middle enterprises. There some significant aspects must be considered in the granting of credit within corporation,i.e firstly, concerning credit mechanism or credit procedure because each of coorperation has different policy in granting credit; secondly, concerning prudential standard. The application of which is trongly significant to provide legal certainty not only for debtor but also creditor (corporation) which covers fit and proper test as well as credit analysis by appling some principles as follows:5C,7P, and 3R and;thirdly, concerning technical resolution toward credit’s default caused by the bad faith’s debtor in performing credit agreement such as taking the available legal procedures as well as using alternative dispute resolution either mediation or negotiation.